2019
DOI: 10.1186/s40550-019-0071-z
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence and antimicrobial resistance profiles of bacterial isolates from meat and meat products in Ethiopia: a systematic review and meta-analysis

Abstract: Background: Foodborne diseases associated with the consumption of meat and its products are of public health significance worldwide. The study is, therefore, aimed to estimate the prevalence and the antimicrobial resistance profile of some bacterial pathogens isolated from meats and its products in Ethiopia. Methods: Literature search was conducted from major electronic databases and indexing services including PubMed/ MEDLINE, Google Scholar, Science Direct and WorldCat. Both published and unpublished studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 44 publications
2
32
0
Order By: Relevance
“…The E. coli O157 occurrence of 6.3% in beef was comparable with the national prevalence estimate (6%) in Ethiopia (Zelalem et al, 2019). This percentage was higher than in studies in other countries that reported 2.2% in Nigeria (Tafida et al, 2014), 0.3% in European Union (EFSA, 2013), 0.8% in the United States (Hill et al, 2011), and 1.7% in Australia (Kiermeier et al, 2011).…”
Section: Discussionsupporting
confidence: 72%
“…The E. coli O157 occurrence of 6.3% in beef was comparable with the national prevalence estimate (6%) in Ethiopia (Zelalem et al, 2019). This percentage was higher than in studies in other countries that reported 2.2% in Nigeria (Tafida et al, 2014), 0.3% in European Union (EFSA, 2013), 0.8% in the United States (Hill et al, 2011), and 1.7% in Australia (Kiermeier et al, 2011).…”
Section: Discussionsupporting
confidence: 72%
“…In a systemic and meta-analysis study done in foods of animal origin (beef, milk, mutton, chevon, and chicken) and environmental swabs in Ethiopia, the estimated pooled prevalence of E. coli was 15% [ 39 ] which is less than that reported in the present study. On the contrary, meta-analysis study done on E. coli O157 : H7 found 4% prevalence in foods of animal origin [ 40 ] and 5% pooled prevalence of E. coli O157 : H7 [ 41 ]. This discrepancy may be due to difference in study subjects, and detection method, or true prevalence.…”
Section: Discussionmentioning
confidence: 99%
“…Bacteria are the causative agent of two-thirds of food-borne disease outbreaks though there have been around 250 different food-borne diseases [ 31 ]. From the biological hazards, bacterial pathogens are the most serious concern regarding the issues of meat safety to consumers [ 32 ]. Bacterial food-borne illnesses are among the most widely spread global public health problems in recent times [ 8 ].…”
Section: Food-borne Zoonotic Bacterial Pathogensmentioning
confidence: 99%